ANALISIS EFEKTIFITAS DAN EFESIENSI PERBEDAAN PENAMPANG PONDASI TIANG YANG DIPANCANG PADA TANAH PASIR - Aribudiman, I Nyoman (Jurnal Ilmiah Teknik Sipil; Vol 26 No 2 (2022): Jurnal Ilmiah Teknik Sipil, Vol. 26 No. 2, Juli 2022DO - 10.24843/JITS.2022.v26.i02.p05, 2022)
The foundation is the lower part of the structure which functions to continue the load of the upper structure as a result of the forces that occur in the upper structure. The choice of foundation type is influenced by the location of the hard soil depth. The amount of bearing capacity is also influenced by the cross-sectional shape of the foundation. In this study, a pile foundation with square, triangular, and circular sections and a drill pile was compared to obtain a foundation alternative that was more effective with different sections in terms of strength with relatively the same cross-sectional area and more efficient in terms of implementation in the field and at a lower cost economical. This research took a case study on the Inna Sanur Beach Hotel Development Project with clay and sand conditions. The calculation of the carrying capacity of a single pile foundation is carried out by taking the calculation of the bearing capacity based on the SPT value and the sondir value. The maximum load received by the piles in the group is calculated so that it is not greater than the carrying capacity of a single pile. The pile foundation with square sections has the largest bearing capacity of the pile group and the drill pile has the smallest bearing capacity of the pile group. The maximum load control received by the pile group is smaller than the carrying capacity of a single pile foundation so that the structure is safe. In terms of implementation, the pile foundation is more efficient and more economical than the bored pile foundation.